A multicellular self-organized probiotic platform for oral delivery enhances intestinal colonization - Hua Liu; Zhijie Chen; Qiaowen Lin; Yi Chen; Liwen Hong; Jie Zhong; Zhengwei Cai; Zhengting Wang; Wenguo Cui (Nature Communications)
Abstract Stable gut colonization of probiotics is essential for sustained therapeutic effects, however traditional oral probiotic supplements often fail to adapt to the gut environment. Here, based on the observation that multicellular microcolonies instead of planktonic bacteria display a more advantageous gene pattern for colonization, we design a system encapsulating multicellular self-organized probiotic microcolonies, termed Express Microcolony Service (EMS), for efficient oral delivery and enhanced gut colonization of probiotics. Utilizing the stress-relaxing and acid-resistant property of the covalent-ionic crosslinking alginate hydrogel microsphere, the micro-cargo provides tunable nutrient supply and extracellular matrix support to facilitate microcolony self-organization. Notably, we show that the variable spatial constraints of the stress-relaxing hydrogel could modulate the viability and colonization potential of microcolonies. In vitro, bacteria microcolonies in EMS show remarkable resistance to gastric acid, bile salts, and antibiotics, compared with planktonic probiotics. In vivo, the EMS strategy exhibits 89- and 52-fold higher colonization rate in the cecum and colon of mice, compared to conventional oral probiotics. The multicellular self-organized EMS system offers an innovative, efficient and clinically transformable alternative for probiotic therapy.